Learning functions in short-term cocaine users. (June 2019) - Kumar, Danusha Selva; Benedict, Elysia; Wu, Olivia; Rubin, Eric; Gluck, Mark A.; Foltin, Richard W.; Myers, Catherine E.; Vadhan, Nehal P.
Abstract: Objective: This study examined learning functions in short-term cocaine users and control participants. Method: Seventeen active cocaine users (reporting 3.5 mean years of cocaine use) and seventeen non-cocaine-using controls (with similar reported levels of alcohol and marijuana use) were compared on tasks measuring different aspects of learning. Results: The cocaine users performed more poorly on the Weather Prediction and List-Learning tasks, as well as supplementary executive and psychomotor function tasks, than controls. Conclusions: Individuals with a relatively short duration of cocaine use exhibited moderate weaknesses in probabilistic category learning, verbal learning and psychomotor functions, relative to controls. These weaknesses may underpin difficulty in learning from the probabilistic consequences of behavior and hinder the ability to respond to cognitive-behavioral treatments. Highlights: Learning functions in short-term cocaine users have been understudied. Short-term cocaine users performed worse than controls on probabilistic category and verbal learning tasks. Short-term cocaine users performed similarly to controls on an equivalence learning task. Clinicians should be aware that even short-term cocaine use may be associated with cognitive weaknesses.